Second Hankel Determinant for Certain Subclass of \(p\)-Valent Analytic Function - Ashwini, S.; Salestina, M. Ruby; Vijaya, Kaliappan (Communications in Mathematics and Applications, 2024)
The aim of this paper is to find sharp upper bound for the Second Hankel determinant and Fekete-Szegö functional for certain subclass of \(p\)-valent analytic function.
Keywords: p-valent analytic function; Second Hankel determinant; Fekete-Szegö functional